A Blockchain-Based Secure Message Routing Framework for VANETs with Trusted Computing Integration - Charan Singh Meena (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Vehicular Ad Hoc Networks (VANETs) enable timely inter-vehicle (V2V) and vehicle-to-infrastructure (V2I) communication to improve road safety and traffic efficiency. However, their high mobility, dynamic topology, and open wireless medium expose VANETs to many attacks: malicious vehicles can inject false safety information or modify messages, potentially causing accidents and loss of life. Traditional security schemes (e.g. public-key infrastructures and authentication protocols) alone may not address all threats in this decentralized, resource-constrained environment. To address these challenges, we propose a novel framework that integrates blockchain technology with trusted computing (hardware-based trust anchors) for secure multi-hop message routing in VANETs. In our design, vehicles and roadside units (RSUs) form a consortium blockchain that immutably records credentials, message hashes, and trust values. Vehicles’ on-board units (OBUs) and RSUs employ Trusted Platform Modules (TPMs) or Trusted Execution Environments (TEEs) to ensure that message-handling software has not been tampered with, binding cryptographic keys to trusted hardware. The combined use of distributed ledger and hardware roots-of-trust prevents identity spoofing and false data injection, while enabling decentralized trust management. We detail the architecture, algorithms, and message flows of the system, and present a simulation study (using Veins/OMNeT++ with realistic VANET mobility) to evaluate performance. Results show the proposed scheme achieves high packet delivery ratio (~94% with 100 nodes, even under attack) and low end-to-end delay (~0.13s) outperforming benchmark protocols. Key contributions include the integration of trusted computing into VANET routing, a blockchain-based trust and revocation infrastructure, and demonstration of robust security against attacks.